2021
DOI: 10.1101/2021.02.08.21251366
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Survey of symptoms following COVID-19 vaccination in India

Abstract: Background: COVID-19 vaccines have been rolled out recently in several parts of the world. Although the protective efficacy is frequently discussed, little is known about the real-world post-vaccination experience outside of clinical trial conditions. Knowledge about what to expect after vaccination will help educate the public, dispel misinformation and reduce vaccine hesitancy. Aim: 1. To assess the immediate response to the first dose of COVID-19 vaccine. 2. To study the spectrum of post-vaccination symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
71
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 8 publications
31
71
7
1
Order By: Relevance
“…but it is not considered a reliable sign of a desirable immune response [27]. Similar to our results showed in various studies on COVID-19 vaccine side effects [16,24,28], Moreover, according to the Centers for Disease Control and Prevention (CDC), side effects tend to be more noticeable after the first dose [29].…”
Section: Discussionsupporting
confidence: 82%
“…but it is not considered a reliable sign of a desirable immune response [27]. Similar to our results showed in various studies on COVID-19 vaccine side effects [16,24,28], Moreover, according to the Centers for Disease Control and Prevention (CDC), side effects tend to be more noticeable after the first dose [29].…”
Section: Discussionsupporting
confidence: 82%
“…The included research articles in this systematic review, confirms the overall safety of vaccines available. Anaphylaxis is rare, indicated by an incidence of <0.001% in large, vaccinated populations in the United States [49,53]. However, when reviewing electronic records of reports of adverse events by individuals presenting to clinicians post-vaccination, the frequency of adverse events was found to be much lower compared to systems that use active surveillance, such as in clinical trials [45].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 26 included peer-reviewed articles, ten were from Israel [30][31][32][33][34][35][36][37][38][39] and eight from the USA [40][41][42][43][44][45][46][47][48]. Six articles looked at adverse event data [42][43][44][45]49] and five looked at vaccine acceptance [46,47,[50][51][52].…”
Section: Peer-reviewed Research Of Vaccination Outcomesmentioning
confidence: 99%
“…However, the findings of this survey do not suggest any difference in symptoms among those who had COVID-19 infection in the past. 10 A retrospective study from Korea included 994 health care workers who took the ChAdOx1 nCoV-19 vaccine (where the data was collected using mobile vaccine adverse events reporting system), has also shown that the severity of most AEFIs to be mild-to-moderate and the severity of AEFI to be less in older age group. 11 Our study has shown that the severity of AEFI was moderate in intensity in the majority of the population.…”
Section: Discussionmentioning
confidence: 99%